Fanfiction: Morality Challenges in Hyperreality Worlds - Permata Widjayanti, Ellita; Anwar, Chaerul (KnE Social Sciences, 2020)
In 4.0 era, in which popular culture is flourishing, fanfiction is experiencing rapid growth. Many fans write about their idols, characters in movies, anime, games, and TV series. They make simulations, create simulacra, and hyperreality. Unfortunately, there are many fan-fiction productions which have pornographic content that is not in accordance with Indonesian cultural norms and moral ethics. This then becomes a moral challenge for the nation, especially for the youth, as they have free access to the internet. This research aims to look the challenges of morality within fanfiction, explaining it through the theory of hyperreality by using data taken from popular fanfiction platforms. The results show that pornography contained in fanfiction poses a threat to the moral codes of teenage readers, and renders pornographic practices more common. Besides, the hyperreality fosters sexual fantasies, which may lead to sexual harassment, free sex, and deviant sex. Keywords: fanfiction, simulation, simulacra, hyperreality, pornography, morality